AN ANALYSIS OF STUDENTS’ STRATEGIES IN ANSWERING TOEFL - Nunung Nurhayati; Berita Nehe (Journal of English Language Studies, 2016)
This article aims at describing types of TOEFL questions seem the most difficult to be answered, the strategies used in answering each type of TOEFL questions, and  the TOEFL score of the 8th semester of English Students in STKIP Setia Budhi Rangkasbitung Academic Year 2015/2016. TOEFl test, questionnaires, and interview were used as the instruments. The results showed that understanding idiom in listening, question of noun forms in structure and written expression, and reference question in reading comprehension are the most difficult question types.  Related to the strategy, various ways are used in answering the TOEFL test. In addition, the TOEFL score of the eighth semester students of STKIP Setia Budhi was low.